2006
DOI: 10.1108/09555340610663728
|View full text |Cite
|
Sign up to set email alerts
|

Constraints facing small western firms in transitional markets

Abstract: Purpose -To provide an Asia-Pacific viewpoint of the key constraints associated with large geographic distances for smaller westerns firms entering central and eastern Europe (CEE), described as a turbulent transitional environment. Design/methodology/approach -An exploratory study was used within a qualitative methodology, using eight case studies across multiple industries. Semi-structured interviews were the main method of data collection conducted in 2003/2004. Open, axial and selective coding was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 62 publications
0
20
1
Order By: Relevance
“…This result does not support the hypothesis of the study, H2. However, this finding is inconsistent with the viewpoints of researchers such as Al-Hyari et al (2012), Freeman and Reid (2006), Huggins (2000), Kitching (2006) and Mag and Varothayan (2015), who reported that government regulations are an outside factor affecting firm performance. Furthermore, the result is inconsistent with an institutional theory which assumes the impact of government and professional associations on the outcomes of organisation (DiMaggio and Powell, 2000;Mizruchi and Fein, 1999).…”
Section: Discussion Of Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…This result does not support the hypothesis of the study, H2. However, this finding is inconsistent with the viewpoints of researchers such as Al-Hyari et al (2012), Freeman and Reid (2006), Huggins (2000), Kitching (2006) and Mag and Varothayan (2015), who reported that government regulations are an outside factor affecting firm performance. Furthermore, the result is inconsistent with an institutional theory which assumes the impact of government and professional associations on the outcomes of organisation (DiMaggio and Powell, 2000;Mizruchi and Fein, 1999).…”
Section: Discussion Of Resultscontrasting
confidence: 74%
“…This can consequently impact the national economic performance on the whole (Fiori et al, 2012). Freeman and Reid (2006) found that government regulations and bureaucracy were a key constraint facing small firms in Europe. Also, in investigating the impact of regulation on the performance of small firms, Kitching (2006) reported that regulation has both direct and indirect significant impact on organisational performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In this study, the case firms were well prepared for the impact of psychic distance because the Japanese market is well known of its entry barriers and cultural differences (cf. Freeman and Reid, 2006). However, by analyzing entries to other major markets or nearby markets would give information of the impact of the so-called psychic distance paradox (O'Grady and Lane, 1996), different strategies applied, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Large firms may perform better in international market as compare to small firms because of better financial position. Freeman and Reid (2006) indicated that, lack of "financial resources" influence the internationalization process of SMEs. Saixing et al (2009) have proposed that, high-level managers, the management expertise and the capacity of financing are crucial factors in internationalization.…”
Section: Internationalization Of Sme'smentioning
confidence: 99%